Tidal amplitude and fish abundance in the mouth region of a small estuary. Issue 3 (20th June 2016) - Becker, A.; Whitfield, A. K.; Cowley, P. D.; Cole, V. J.; Taylor, M. D.
Abstract : Using an acoustic underwater camera (Dual Frequency IDentification SONar, DIDSON), the abundance and direction of movement of fishes > 80 mm total length ( L T ) in the mouth of a small South African estuary during spring and neap tidal cycles were observed. While the sizes of fishes recorded were consistent across both tide cycles, the number of fishes passing the camera was significantly greater during the smaller neap tides. Schooling behaviour was more pronounced for fishes that were travelling into the estuary compared to fishes swimming towards the ocean.